Negotiating Difference in Krishen Jit's Theatre: Staging Identities and Contesting Boundaries in Multicultural Malaysia - Charlene Rajendran, (Wacana Seni Journal of Arts Discourse, 2012)
The politics of difference in a multicultural society such as Malaysia is an area of increasing interest in an environment of global anxieties about the "clash of civilisations" (Huntington) and the "flows of culture" (Appadurai). As the lines of race, religion, language and gender become more prescribed by the "authorities" of state and media, they are also diversely contested by those who do not fit or who choose to resist these narrow defines and limiting dictates. Krishen Jit, doyen of Malaysian theatre, dealt with issues of difference and sameness in his multiple staging of Malaysian identities. His theatre process and practice were in several ways critical interventions into the Malaysian cultural landscape. This article will examine some of the strategies used in Krishen Jit's theatre that dealt with cultural difference and emerged as a valuable response to the tensions of identity in Malaysia. It interrogates his choices for theatre and how they indicate a conscious engagement with issues of plural identities within a multicultural mosaic. It seeks to offer a perspective on how the theatre provides an apt site for questions of agency and belonging that arise in negotiating issues of exclusion and inclusion within a plural socio-cultural space.